2015
DOI: 10.7287/peerj.preprints.1531v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the psychometric properties of the English version of the Internet Addiction Test in the Pakistani population: a cross-sectional survey

Abstract: Introduction: Despite growing concerns over pathological use of the Internet, studies based on validated psychometric instruments are still lacking in Pakistan. The present study aimed to examine the psychometric properties of Young’s Internet Addiction Test (IAT) in a sample of the Pakistani population. We examined the validity, internal consistency, readability and floor and ceiling effects of IAT scores.Methods: This cross-sectional study was conducted at CMH Lahore Medical College and Institute of Dentistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous Pakistani studies concluded that the proportion of addictive internet users ranged from 0.6% to 1.1%, and the proportion of problematic internet users ranged from 16% to 37% before the COVID-19 pandemic. [54][55][56] The findings from the current study are showing higher proportions among problematic and addictive internet users as compared to pre-COVID times. The possible reason for the rise in internet addiction could be the measures taken to curb the COVID-19 pandemic such as lockdowns, closure of educational institutions, closure of entertainment clubs, and promotion of work from home practices have led to an increase in time spent at home and have contributed remarkably in increased and possibly addictive use of the internet.…”
Section: Discussionmentioning
confidence: 46%
“…Previous Pakistani studies concluded that the proportion of addictive internet users ranged from 0.6% to 1.1%, and the proportion of problematic internet users ranged from 16% to 37% before the COVID-19 pandemic. [54][55][56] The findings from the current study are showing higher proportions among problematic and addictive internet users as compared to pre-COVID times. The possible reason for the rise in internet addiction could be the measures taken to curb the COVID-19 pandemic such as lockdowns, closure of educational institutions, closure of entertainment clubs, and promotion of work from home practices have led to an increase in time spent at home and have contributed remarkably in increased and possibly addictive use of the internet.…”
Section: Discussionmentioning
confidence: 46%